De-Classrooming: Moving Learning Outside the Classroom - Andrew P. Carlin (PRISM)
This paper reflects on a teaching problem highlighted as part of a second-year undergraduate module in sociology, taught at a UK based institution of higher education. The specific teaching problem – that of student learning as encountered and revealed in seminars – was nested within other issues; some of which related to the characteristics of the discipline of sociology itself, whilst others, related to more localised issues such as the choice of materials available for students to access and download. Whilst the lecture and course material was fixed, the flexibility of the seminar framework enabled the exploration and implementation of an ad hoc intervention in the form of ‘de-classrooming’. This intervention was utilised and developed to enhance the knowledge base and conceptual understanding of the student cohort in relation to “Everyday Life” sociology. The ‘de-classrooming’ intervention proved to be an efficacious pedagogic device, which facilitated dynamic levels of flexibility and creativity by both teacher and learners. As a pedagogic device, it manifested a number of key benefits: such as aiding the clarification of conceptual confusions. Ultimately, the de-classrooming intervention operated to establish an empowered sense of ownership where knowledge and knowledge-generation were concerned, and afforded students unorthodox opportunities for learning enhancement.